2012
DOI: 10.1111/j.1475-6811.2012.01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of similarity of life goals, values, and personality on relationship satisfaction and stability: Findings from a two‐wave panel study

Abstract: Using data from the German Family Panel (pairfam; n = 3,674 heterosexual couples), this study examines the impact of partners' individual levels and dyadic similarity concerning life goals, values, and personality traits on relationship satisfaction and union dissolution. Controlling for partners' individual characteristics and for relationship duration, it was found that similarity on specific dimensions and stereotype-adjusted profile correlations exerted significant yet small positive effects on both partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 64 publications
1
40
1
Order By: Relevance
“…Attitudes regarding gender roles and family life, as well as interpersonal interaction styles, have been found to affect relationship quality (Amato & Booth, 1995;Chi et al, 2013;Faulkner, Davey, & Davey, 2005;Oldenbak & Figueredo, 2009). Emotional support and companionship are well-known sources of marital happiness and are likely to be fostered by shared norms and attitudes (Acitelli, Kenny, & Weiner, 2001;Arránz Becker, 2013;Luo & Klohnen, 2005;Stutzer & Frey, 2006).…”
Section: Subjective Well-being: Life Satisfaction and Relationship Samentioning
confidence: 99%
See 4 more Smart Citations
“…Attitudes regarding gender roles and family life, as well as interpersonal interaction styles, have been found to affect relationship quality (Amato & Booth, 1995;Chi et al, 2013;Faulkner, Davey, & Davey, 2005;Oldenbak & Figueredo, 2009). Emotional support and companionship are well-known sources of marital happiness and are likely to be fostered by shared norms and attitudes (Acitelli, Kenny, & Weiner, 2001;Arránz Becker, 2013;Luo & Klohnen, 2005;Stutzer & Frey, 2006).…”
Section: Subjective Well-being: Life Satisfaction and Relationship Samentioning
confidence: 99%
“…In the literature on couple similarity and well-being a variety of different predictors have been used, ranging from personality characteristics, which have received by far the most research attention (Arránz Becker, 2013;Arrindell & Luteijn, 2000;Dyrenforth, Kashy, Brent, & Lucas, 2010;Gonzaga, Campos, & Bradbury, 2007;Gonzaga, Carter, & Buckwalter, 2010;Shiota & Levinson, 2007); demographic characteristics, such as age and education (Tynes, 1990;Watson et al, 2004); to attitudes, norms, and values (Acitelli, Kenny, & Weiner, 2001;Heaton & Pratt, 1990). Some studies have found similarity between partners to be associated with marital satisfaction (e.g., Wilson & Cousins, 2003), whereas in others little or no such association has been found (Luo, 2009;Luo et al, 2008;Luo & Zhang, 2009;Watson et al, 2004).…”
mentioning
confidence: 99%
See 3 more Smart Citations